Tunable strain effects on the electronic structures and mobility properties of InP/InAs lateral heterostructure. (9th October 2020) - Lin, Long; Li, Shaofei; Yao, Linwei; Yu, Weiyang; Cai, Xiaolin; Zhang, Liwei; Zhang, Wei-Bing; Zhang, Zhanying; Tao, Hualong
Abstract: Two-dimensional lateral heterostructures (LHSs) carry unconventional physical properties due to their excellent adjustable band-offset and sensitive interface characteristics. In this paper, we have designed two kinds of seamless LHSs with excellent stabilities, the zigzag-zigzag (Z-Z) InP/InAs LHS and the armchair-armchair (A-A) InP/InAs LHS, and the changes in lattice structures and electronic properties under different strains are studied systematically by employing first-principles calculations based on density functional theory. Our results indicate that the Z-Z and A-A InP/InAs LHSs are indirect-bandgap semiconductors with a moderate bandgap. Surprisingly, it is found that the carrier mobility of holes for the Z-Z InP/InAs LHS is as high as 6.954 × 10 3 cm 2 · V −1 · s −1 . The established Z-Z and A-A InP/InAs LHSs exhibit superior properties under uniaxial strains ( a -direction and b -direction) and biaxial strain ( ab -direction). It is found that the conduction bands of Z-Z and A-A InP/InAs LHSs occur with an intriguing downward (upward) transfer under compressive (tensile) strain along the b- and ab -directions, respectively. Moreover, when more than 2% of the tensile strain along the ab -direction is applied, the Z-Z and A-A InP/InAs LHS change from an indirect bandgap semiconductor to a direct bandgap semiconductor, and the Z-Z InAs/InP LHS changes into type-II heterostructure. Based on the calculated band structures, the effect of uniaxial strain on effective mass is anisotropic. Especially when tensile strain is applied, the effective mass of electrons in Z-Z and A-A InP/InAs LHSs will be reduced, which is consistent with the change in band structures under strain. The strain tunability of direct bandgap, type-II band alignment, and high carrier mobility mean Z-Z and A-A InP/InAs LHSs have potential applications in optoelectronic, photovoltaic, and flexible electronic devices.